MIKROANATOMI LIMPA TIKUS PUTIH (Rattus novergicus L.)SETELAH PEMBERIAN ASAM HUMAT DARI TANAH GAMBUT KALIMANTAN - Wulandari Rousdy, Diah; Rahmawati; Kurniatuhadi, Rikhsan; Kurniadi, Edi (JURNAL BORNEO AKCAYA, 2017)
Peat soil is organic soil types that has various biological potential to be developed. Humic acid compounds in the peat soil have a variety of potential biological one as immunostimulant. The aimed of this study to determine the effect of humic acid extracted from peat soil spleen histology Kalimantan against white male rats (Rattus novergicus L.) strain Wistar. Peat soil samples were taken in Pontianak on sapris maturity level. Humic acid is separated from other humic substances using IHSS methode. This research was done by completely randomized design with 4 treatments ie positive control (isoprinosin 380,3 mg/kg), humic acid 125; 250; 500 mg / kg body weight. Humic acid was administrated by oral gavage for 10 days. After 10 days, spleen organ was taken to preparat by paraffin methode and hematoxilin-eosin staining. Humic acid administration of 125 mg/kg showed a larger diameter than the white pulp isoprinosin control. However, humic acid administration of 500 mg/kg caused the excess stimulation of white pulp of the spleen congestion symptoms characterized by disarrangenment of lymphocytes cluster. There are no significant different of spleen weight between all treatments